Long-term outcomes of coils embolization for superior hypophyseal artery aneurysms - Kang, Yan-Po; Li, Cheng-Yu; Chen, Chun-Ting; Yeap, Mun-Chun; Wong, Ho-Fai; Wu, Yi-Ming; Hsieh, Po-Chuan; Liu, Zhuo-Hao; Chuang, Chi-Cheng; Chen, Ching-Chang (Frontiers in Neurology, 2023)
Objective Superior hypophyseal artery (SHA) aneurysms are intradural, and their rupture can result in subarachnoid hemorrhage. Considering the related surgical difficulty and anatomical restrictions, endovascular treatment (EVT) is considered the most favorable modality for SHA aneurysms; however, the long-term outcomes of EVT have rarely been reported. The study assessed the incidence of and risk factors for recurrence of SHA aneurysms after EVT as well as the correlation factors for SHA aneurysm rupture. Methods We included 112 patients with SHA aneurysms treated with EVT at our facility between 2009 and 2020. Here, EVT included non–stent-assisted (simple or balloon-assisted) or stent-assisted coiling. Flow diverter was not included because it was barely used due to its high cost under our national insurance’s limitation, and a high proportion of ruptured aneurysms in our series. Univariate and multivariate logistic regression was performed to evaluate the correlation factors for SHA aneurysm rupture, along with the incidence of and risk factors for post-EVT SHA aneurysm recurrence and re-treatment. Results In our patients, the mean angiographic follow-up period was 3.12 years. The presence of type IA or IB cavernous internal carotid artery (cICA) was strongly correlated with SHA aneurysm rupture. Recurrence occurred in 17 (13.4%) patients, of which only 1 (1.4%) patient had received stent-assisted coiling. All cases of recurrence were observed within 2 years after EVT. The multivariate logistic regression results showed that ruptured aneurysm and non–stent-assisted coiling were independent risk factors for aneurysm recurrence. Of the 17 cases of aneurysm recurrence, 9 (52.9%) received re-treatment. Moreover, aneurysm rupture was the only factor significantly correlated with re-treatment in multivariate logistic regression. No re-recurrence was observed when a recurrent aneurysm was treated with stent-assisted coiling. Conclusion Type I cICA was common factor for aneurysm rupture. Although flow-diverter treatment serves as another suitable technique that was not compared with, coils embolization was effective treatment modality for SHA aneurysms, leading to low recurrence and complication rates, especially with stent use. All cases of recurrence occurred within 2 years after EVT; they were strongly associated with prior aneurysm rupture. Further stent-assisted coiling was noticed to prevent re-recurrence.